Rapid green synthesis of noncytotoxic iron oxide nanoparticles using aqueous leaf extract ofThymbra spicataand evaluation of their antibacterial, antibiofilm, and antioxidant activity - Erci, Fatih; Cakir-Koc, Rabia (TAYLOR & FRANCIS INC, 2021)
Herein the green synthesis of iron oxide (FeO) nanoparticles (NPs) was achieved by usingThymbra spicataleaf extract. The antibacterial activity of FeONPs was evaluated against both gram-positive and gram-negative bacteria by using broth microdilution assay. Further, the antioxidant and cytotoxic potential of FeONPs was determined by using standard protocols. The effects of nanoparticles onStaphylococcus aureusgrowth and on their biofilm formation were investigated. FeONPs at the concentration of 100 mu g/mL exhibited excellent bactericidal action againstSalmonella typhimurium. Also, the biogenic nanoparticles inhibited the growth rate ofS. aureus.Furthermore, FeONPs showed noncytotoxic characteristics on L929 mouse fibroblast cells. All these results revealed that FeONPs obtained by simple and eco-friendly synthesis process throughT. spicataextract could be considered a promising candidate as antibacterial agent for many different applications. Also, biogenic FeONPs with their antibiofilm activity onS. aureuscould serve as potent antibacterial agents against pathogenic biofilm-forming bacteria.
Keywords: Thymbra spicata; iron oxide nanoparticles; antibacterial; antibiofilm; cytotoxicity; ESSENTIAL OILS; BIOGENIC SYNTHESIS; THYMBRA; FABRICATION; FRUIT; SIZE; Chemistry; Science & Technology - Other Topics